Hubungan Pengetahuan dan Sikap Siswa SMAN 3 Padang dengan Tingkat Kecemasan terhadap Covid-19 - Renidayati Reni; N. Rachmadanur; Meliza Ella Qadrina (Jurnal Sehat Mandiri, 2023)
Student anxiety about Covid-19 is a signal to alert and warn someone of the dangers that threaten to relate to Covid-19. Anxiety about Covid-19 can happen to anyone, including teenagers. The negative impact of this anxiety is excessive anxiety. This study aims to determine the relationship between the knowledge and attitudes of SMAN 3 Padang students with the level of anxiety about Covid-19. This research is an analytic study, with a cross sectional. The population in this study were all students of class X-XI SMAN 3 Padang as many as 704 students. Sampling was done by simple random sampling with a total sample of 98 respondents. The research was carried out in January-June 2022, where the research location was at SMAN 3 Padang. data collection using a questionnaire. Data analysis includes univariate and bivariate. This study found that 54.1% of respondents felt anxious, 56.1% of respondents had less knowledge regarding Covid-19, and 65.3% of respondents had negative attitudes regarding Covid-19. A significant relationship was found between knowledge and anxiety (p-value= 0.000), and a significant relationship was found between attitudes and anxiety (p-value= 0.000). Based on the results of the study, it can be concluded that knowledge and attitudes contribute to student anxiety during the Covid-19 period. Students are advised to be able to control anxiety by consulting with BK, enriching knowledge about preventing Covid-19, and implementing health protocols.